Lennert’s lymphoma - a diagnostic dilemma: a case report and pathologic review of literature - Kapoor, Akhil; Beniwal, Surender; Purohit, Ramesh; Kumar, Vanita; Kumar, Harvindra Singh (International Journal of Advances in Medicine, 2017)
Lymphoepitheloid lymphoma, also referred to as Lennert’s lymphoma is a T-cell lymphoma characterized by the massive proliferation of epithelial cell clusters infiltrating normal lymph nodal architecture along with lymphoid cells. Epithelial cells can also be associated with infectious lymphadenopathy and Hodgkin’s lymphoma. This presents a diagnostic dilemma. We present a case of Lennert’s lymphoma along with review of literature with special emphasis on morphological features and immmunohistochemistry findings.